Analysis of The Effect of PBL-Based Experimental and Project Methods on Science Learning Achievement - Ulin Nuha Rosyida; Sukarmin Sukarmin; Widha Sunarno (Universitas Negeri Makassar, 2019)
This research aim was to find out the interaction between Problem Based Learning with experimental and project methods with thinking skill toward student’s cognitive learning outcomes. This research was held in SMP A on second semester of 2017/2018. The type of this research was experimental research. This research’s subject was 55 7th grade students, determined with the cluster random sampling technique. Data were collected using test technique. Analysis technique was using quantitative analysis with two-way analysis of variance. Based on the results, in the first hypothesis the result means that there was difference between the student’s cognitive learning achievement with Problem Based Learning with the project method and experimental method. In the second hypothesis, the result means that there was difference between student’s cognitive learning achievement which have higher order thinking skill and lower order thinking skill. In the third hypothesis, the result means no interaction between Problem Based Learning with experimental method and project method with thinking skill toward student’s cognitive learning achievement.